2015
DOI: 10.1242/bio.201410850
|View full text |Cite
|
Sign up to set email alerts
|

H3K36 Trimethylation-Mediated Epigenetic Regulation is Activated by Bam and Promotes Germ Cell Differentiation During Early Oogenesis in Drosophila

Abstract: Epigenetic silencing is critical for maintaining germline stem cells in Drosophila ovaries. However, it remains unclear how the differentiation factor, Bag-of-marbles (Bam), counteracts transcriptional silencing. We found that the trimethylation of lysine 36 on histone H3 (H3K36me3), a modification that is associated with gene activation, is enhanced in Bam-expressing cells. H3K36me3 levels were reduced in flies deficient in Bam. Inactivation of the Set2 methyltransferase, which confers the H3K36me3 modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…In the present study, levels of H3K36me3 in cattle-yaks were significantly lower than those in yaks. Low levels of H3K36me3 have probably repressed meiosis and blocked germ cell differentiation in cattle-yaks [25,50]. Levels of KDM4B and H3K36me3 were both lower in cattle-yaks compared with yaks, and these results do not appear to be consistent with findings that the levels of H3K36me3 were significantly decreased after inducible expression of KDM4B [47].…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In the present study, levels of H3K36me3 in cattle-yaks were significantly lower than those in yaks. Low levels of H3K36me3 have probably repressed meiosis and blocked germ cell differentiation in cattle-yaks [25,50]. Levels of KDM4B and H3K36me3 were both lower in cattle-yaks compared with yaks, and these results do not appear to be consistent with findings that the levels of H3K36me3 were significantly decreased after inducible expression of KDM4B [47].…”
Section: Discussionmentioning
confidence: 60%
“…The function of H3K36me3 is related to transcriptional activation [49]. In related studies, the level of H3K36me3 plays important roles in germ cell differentiation, somatic cell reprogramming, and chromosome recombination [25,47,50]. It was reported that normal methylation levels of H3K36me3 are required for spermatogenesis and sperm differentiation [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As several regulators of histone modifications are essential for germline development (Clough et al, 2007;Mukai et al, 2015), we found that both CBP and HDAC1 preferentially interacted with MamoAF (Figure 1). Additionally, since CBP is responsible for H3K27ac (Creyghton et al, 2010;Stasevich et al, 2014;Tie et al, 2009) and HDAC1 is required for the deacetylation of H3K27ac (Tie et al, 2009), we can say that proper regulation of H3K27ac levels may play an essential role in germline development.…”
Section: Discussionmentioning
confidence: 89%